Resin composition, resin composition for hard coat, release coating agent composition, cured product, laminate, and method for manufacturing recycled base material

JP2025029316APending Publication Date: 2025-03-06ARAKAWA CHEM IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023133865
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-03-06

AI Technical Summary

Benefits of technology

【0013】 本発明の樹脂組成物の硬化物は、アルカリ溶液に対して溶解し、当該硬化物と積層体を構成していた基材を分離してリサイクルすることできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029316000001
    Figure 2025029316000001
Patent Text Reader

Abstract

To provide a resin composition from which a cured product dissolvable in an alkali solution can be provided, a resin composition for hard coat, and a release coating agent composition.SOLUTION: There are provided a resin composition which contains a polymerizable monomer (A) containing poly(meth)acrylate (a1) having no carboxyl group and a hydroxy group having weight average molecular weight of 170 or more and 250 or less, and a (meth)acrylic copolymer (B) that is a reaction product of a polymer (b1) of a polymerization component containing an unsaturated monomer having an epoxy group and an α,β-unsaturated carboxylic acid (b2), and has a (meth)acrylic equivalent of 200 to 270 g / eq; and a hard coat resin composition, a release coating agent composition, a cured product, and a laminate which contain the composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a resin composition for hard coat, a release coating composition, a cured product, a laminate, and a method for producing a recycled substrate. [Background technology]

[0002] In recent years, with the rise in awareness of environmental protection, there has been an increasing demand for recycling substrates from articles, and for example, the methods described in Patent Documents 1 and 2 have become publicly known. However, Patent Document 1 requires equipment for crushing and pumping, and Patent Document 2 requires multiple steps, so there is a demand for a simpler method for recycling substrates. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2022-068217 [Patent Document 2] Special Publication No. 2022-544275 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a resin composition which gives a cured product which can be dissolved in an alkaline solution, a resin composition for hard coating, and a release coating composition. [Means for solving the problem]

[0005] As a result of extensive investigations, the present inventors have found that a specific resin composition can solve the above problems.

[0006] 1. A (meth)acrylate (A) containing a poly(meth)acrylate (a1) having no carboxyl group and a hydroxy group and having a weight average molecular weight of 170 or more and 250 or less, and A resin composition comprising a (meth)acrylic copolymer (B) having a (meth)acrylic equivalent of 200 to 270 g / eq, the (meth)acrylic copolymer (B) being a reaction product of a polymer (b1) of polymerization components containing an unsaturated monomer having an epoxy group and an α,β-unsaturated carboxylic acid (b2).

[0007] 2. The resin composition according to item 1, wherein the content ratio of the component (A) to the component (B) [component (A) / component (B)] is 5 / 95 to 95 / 5, in terms of non-volatile mass.

[0008] 3. A resin composition for hard coat comprising the resin composition according to item 1 or 2 above.

[0009] 4. A release coating composition comprising the resin composition according to item 1 or 2 above.

[0010] 5. A cured product of the resin composition described in the preceding paragraph 1 or 2.

[0011] 6. A laminate comprising a substrate and the cured product described in 5 above.

[0012] 7. A method for producing a recycled substrate, comprising the step of removing the cured product described in item 5 above by contacting the laminate described in item 6 above with an alkaline solution. Effect of the Invention

[0013] The cured product of the resin composition of the present invention dissolves in an alkaline solution, and the cured product can be separated from the substrate constituting the laminate and recycled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The resin composition of the present invention contains a (meth)acrylate (A) (hereinafter referred to as component (A)) which contains a poly(meth)acrylate (a1) (hereinafter referred to as component (a1)) which has no carboxyl group and has a hydroxy group and a weight average molecular weight of 170 or more and 250 or less, and a specific (meth)acrylic copolymer (B) (hereinafter referred to as component (B)). Furthermore, (meth)acrylate refers to methacrylate or acrylate, and when there are a plurality of (meth)acrylates, it means that each may independently include methacrylate or acrylate (the same applies below). Furthermore, (meth)acrylic refers to methacryl or acrylic, and when there are a plurality of (meth)acrylics, each of them may independently have methacryl or acrylic (the same applies below).

[0015] The component (a1) is a poly(meth)acrylate that has no carboxyl groups but has hydroxyl groups. When the component (a1) is contained, the cured product becomes more soluble in an alkaline solution.

[0016] If the component (a1) has a carboxyl group, when a laminate is formed by contacting a metal substrate with the cured product of the present invention, the carboxyl group may react and corrode the metal, which is undesirable.

[0017] Furthermore, if the (a1) component does not have a hydroxy group, the cured product will be less soluble in alkaline solutions and the substrate will not be recyclable. Furthermore, if the (a1) component has one or less (meth)acryloyl group, the cured product will tend to have poor scratch resistance.

[0018] The weight average molecular weight of the (a1) component is 170 or more and 250 or less. The weight average molecular weight is a polystyrene equivalent value by gel permeation chromatography (GPC) (hereinafter the same). When the weight average molecular weight of the (a1) component is 170 or more and 250 or less, the cured product dissolves well in an alkaline solution, making it possible to recycle the substrate. From the same point of view, the weight average molecular weight is more preferably 170 or more and 230 or less.

[0019] Examples of such (a1) components include trimethylolethane di(meth)acrylate, trimethylolpropane diacrylate, erythritol diacrylate, pentaerythritol diacrylate, 1-((meth)acryloyloxy)-3-((meth)acryloyloxy)-2-propanol, and glycerin di(meth)acrylate. As the (a1) component, a mixture of the above-mentioned components with trimethylolethane tri(meth)acrylate, trimethylolpropane triacrylate, erythritol triacrylate, pentaerythritol triacrylate, 1-((meth)acryloyloxy)-2-((meth)acryloyloxy)-3-((meth)acryloyloxy)propane, and glycerin tri(meth)acrylate can also be used. These (a1) components may be used alone or in combination of two or more. Among these, glycerin di(meth)acrylate, and a mixture of glycerin di(meth)acrylate and glycerin tri(meth)acrylate are preferred, since the cured product tends to exhibit excellent scratch resistance and is easily soluble in an alkaline solution.

[0020] The content of the (a1) component relative to 100% by mass of the resin composition is preferably 1% by mass or more and 99% by mass or less, more preferably 3% by mass or more and 97% by mass or less, even more preferably 5% by mass or more and 95% by mass or less, and particularly preferably 60% by mass or more and 95% by mass or less, in terms of non-volatile mass (hereinafter the same) from the viewpoint of making the cured product easily soluble in an alkaline solution. The non-volatile mass refers to the components excluding solvents such as water and organic solvents contained in the resin composition.

[0021] Furthermore, the content of the (a1) component relative to 100% by mass of the (A) component is preferably 1 to 100% by mass, more preferably 3 to 97% by mass, even more preferably 5 to 95% by mass, and particularly preferably 60 to 95% by mass, from the viewpoint of making the cured product more soluble in an alkaline solution.

[0022] The resin composition of the present invention may further contain a (meth)acrylate (a2) (hereinafter referred to as component (a2)) other than the component (a1).

[0023] Examples of the component (a2) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and isooctyl. (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tetradecyl (meth)acrylate (myristyl (meth)acrylate), hexadecyl (meth)acrylate (palmityl (meth)acrylate), octadecyl (meth)acrylate (n-stearyl (meth)acrylate), isostearyl (meth)acrylate and other alkyl mono(meth)acrylates; hydroxyalkyl mono(meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; cycloalkyl mono(meth)acrylates such as cyclohexyl (meth)acrylate, norbornyl (meth)acrylate, isobornyl (meth)acrylate, norbornanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, and tricyclodecane dimethylol di(meth)acrylate; Aryl mono(meth)acrylates such as phenyl(meth)acrylate, benzyl acrylate, 2-phenylethyl(meth)acrylate, nonylphenoxypolyethylene glycol(meth)acrylate, o-phenylphenoxyethyl(meth)acrylate, m-phenylphenoxyethyl(meth)acrylate, p-phenylphenoxyethyl(meth)acrylate, o-phenoxybenzyl(meth)acrylate, m-phenoxybenzyl(meth)acrylate, p-phenoxybenzyl(meth)acrylate, ethoxylated-o-phenylphenol(meth)acrylate, ethoxylated-m-phenylphenol(meth)acrylate, ethoxylated-p-phenylphenol(meth)acrylate, ethylene oxide-modified-o-cumylphenol(meth)acrylate, ethylene oxide-modified-m-cumylphenol(meth)acrylate, ethylene oxide-modified-p-cumylphenol(meth)acrylate, and triphenylmethyl(meth)acrylate; alkanediol di(meth)acrylates such as propanediol di(meth)acrylate, butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, and 1,8-octanediol di(meth)acrylate; Alkylene glycol di(meth)acrylates such as diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; Pentaerythritol(meth)acrylates such as pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; Dipentaerythritol (meth)acrylates such as dipentaerythritol mono(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; Examples of tripentaerythritol (meth)acrylates include tripentaerythritol mono(meth)acrylate, tripentaerythritol di(meth)acrylate, tripentaerythritol tri(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate. These may be used alone or in combination of two or more.

[0024] The content of the (a2) component relative to 100% by mass of the resin composition is preferably 20% by mass or less, and more preferably 10% by mass or less, because the cured product is likely to exhibit excellent scratch resistance and is easily soluble in an alkaline solution.

[0025] The content of the (a2) component relative to 100% by mass of the (A) component is preferably 10% by mass or less, since the cured product tends to exhibit excellent scratch resistance and is easily soluble in an alkaline solution.

[0026] Examples of the physical properties of the component (A) include the hydroxyl value, the viscosity at 25° C., and the (meth)acrylic equivalent.

[0027] The hydroxyl value of component (A) is preferably from 225 mgKOH / g to 330 mgKOH / g, more preferably from 230 mgKOH / g to 300 mgKOH / g, in order to improve the affinity between the cured product and the alkaline solution. The hydroxyl value is a value measured by the neutralization titration method according to JIS K 0070-1992 (hereinafter the same).

[0028] The viscosity of component (A) at 25° C. is preferably from 10 mPa·s to 1,000 mPa·s, and more preferably from 20 mPa·s to 500 mPa·s. The viscosity is measured (for 5 minutes) using an E-type viscometer (product name "TVE-10", manufactured by Toki Sangyo Co., Ltd.).

[0029] Furthermore, the (meth)acrylic equivalent of the (A) component is preferably less than 200 g / eq, more preferably 80 g / eq or more and 150 g / eq or less, in order that the cured product tends to exhibit excellent scratch resistance. The (meth)acrylic equivalent is represented by the non-volatile mass (g) of the component per (meth)acryloyl group (hereinafter the same).

[0030] The content of the (A) component relative to 100% by mass of the resin composition is preferably from 1 to 99% by mass, more preferably from 3 to 97% by mass, even more preferably from 5 to 95% by mass, and particularly preferably from 60 to 95% by mass, because the cured product is easily soluble in an alkaline solution.

[0031] <(B) component> The component (B) is a (meth)acrylic copolymer having a (meth)acrylic equivalent of 200 to 270 g / eq, which is a reaction product of a polymer (b1) containing an unsaturated monomer having an epoxy group and an α,β-unsaturated carboxylic acid (b2). The component (B) is a component that provides excellent scratch resistance to the cured product. The term "unsaturated" refers to having one or more carbon-carbon double bonds and / or carbon-carbon triple bonds in the molecule (hereinafter the same).

[0032] <(b1) component> The component (b1) is a polymer of a polymerization component containing an ethylenically unsaturated monomer (b1-1) having an epoxy group (hereinafter also referred to as component (b1-1)).

[0033] Examples of the (b1-1) component include (meth)acrylates having an epoxy group such as glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl (meth)acrylate; (meth)acrylates having a hydroxyl group and an epoxy group such as 4-hydroxybutyl (meth)acrylate glycidyl ether; vinyl compounds having an epoxy group such as vinyl glycidyl ether and 1,2-epoxy-4-vinylcyclohexane; and allyl compounds having an epoxy group such as allyl glycidyl ether. These may be used alone or in combination of two or more. Among them, (meth)acrylates having an epoxy group are preferred, and glycidyl (meth)acrylate is more preferred.

[0034] The polymerization components may contain an unsaturated monomer (b1-2) (hereinafter referred to as component (b1-2)) other than the component (b1-1).

[0035] Examples of the (b1-2) component include: Alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate; Monocycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, and cyclooctyl (meth)acrylate; polycycloalkyl (meth)acrylates such as isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 1-adamantyl (meth)acrylate, and 3,5-dimethyladamantyl (meth)acrylate; Aryl (meth)acrylates such as phenyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; Styrenics such as styrene, α-methylstyrene, t-butylstyrene, and dimethylstyrene; Dicarboxylic acid anhydrides having an ethylenically unsaturated group, such as maleic anhydride, itaconic anhydride, citraconic anhydride, and alkenyl succinic anhydride; Examples of the compound include acrylonitrile, (meth)acrylamide, vinyl acetate, etc. These compounds may be used alone or in combination of two or more kinds.

[0036] In addition, as the component (b1-2), a macromonomer having a (meth)acryloyl group, an organopolysiloxane having a (meth)acryloyl group, a macromonomer having a styrene group, a polyalkylene glycol monoalkyl mono(meth)acrylate, etc. can also be used. These may be used alone or in combination of two or more. In addition, examples of commercially available products include "Macromonomer AA-6", "Macromonomer AB-6", "Macromonomer AS-6", and "Macromonomer AW-6S" (all manufactured by Toagosei Co., Ltd.), "X-22-174ASX", "X-22-174BX", "KF-2012", "X-22-2426", and "X-22-2404" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "Silaplane FM-0711", "Silaplane FM-0721", and "Silaplane FM-0725" (all manufactured by JNC Corporation), "Blenmer PME-1000", "Blenmer PME-4000", and "Blenmer PSE-1300" (all manufactured by NOF Corporation), and the like.

[0037] In producing the component (b1), the amounts of the components (b1-1) and (b1-2) used per 100 parts by mass of the total of these components can be adjusted as follows. Component (b1-1): preferably 25 to 100 parts by mass, more preferably 50 to 100 parts by mass Component (b1-2): preferably 75 parts by mass or less, more preferably 50 parts by mass or less

[0038] The component (b2) is an α,β-unsaturated carboxylic acid.

[0039] Examples of the (b2) component include α,β-unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid; and α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid. In addition, the (b2) component may be an acid anhydride of an α,β-unsaturated carboxylic acid or a salt of an α,β-unsaturated carboxylic acid. Examples of the salt include alkali metal salts such as sodium salts and potassium salts; and ammonium salts such as ammonia, methylamine, and ethanolamine. These may be used alone or in combination of two or more. Among them, α,β-unsaturated monocarboxylic acids are preferred, and (meth)acrylic acid is more preferred, in terms of excellent scratch resistance of the cured product.

[0040] The amount of the (b2) component used is preferably 0.5 to 1.2 mol, and more preferably 0.8 to 1 mol, per 1 mol of the (b1-1) component, since this makes it less likely to gel during the reaction and also increases the hardness of the cured product.

[0041] The component (B) can be obtained by reacting the component (b1-1) and, if necessary, the component (b1-2) in the presence of a thermal polymerization initiator to obtain the component (b1), and then adding the component (b2) to carry out an addition reaction.

[0042] As for the reaction conditions for the component (b1), for example, the reaction temperature is usually 50 to 150° C., and preferably 60 to 130° C., and the reaction time is usually 0.5 to 10 hours, and preferably 1 to 5 hours.

[0043] Conditions for the addition reaction of the components (b1) and (b2) include a reaction temperature of usually 70 to 130° C., and preferably 80 to 120° C., and a reaction time of usually 1 to 12 hours, and preferably 2 to 10 hours.

[0044] Examples of the thermal polymerization initiator include inorganic peroxides such as hydrogen peroxide, ammonium persulfate, and potassium persulfate; organic peroxides such as benzoyl peroxide, dicumyl peroxide, and lauryl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile and dimethyl-2,2'-azobisisobutyrate. These may be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.2 to 10 parts by mass relative to 100 parts by mass of the total of the (b1-1) component and the (b1-2) component. If necessary, a chain transfer agent may be added. Examples of the chain transfer agent include lauryl mercaptan, dodecyl mercaptan, 2-mercaptobenzothiazole, and bromotrichloromethane. These may be used alone or in combination of two or more.

[0045] In the above reaction, an organic solvent may further be used.

[0046] Examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; Aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, isooctane, and n-decane; Alicyclic hydrocarbons such as cyclopentane and cyclohexane; Esters such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, and methyl benzoate; Ketones such as methyl ethyl ketone, acetylacetone, methyl isobutyl ketone, isophorone, cyclopentanone, cyclohexanone, and methylcyclohexanone; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether; Alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, t-butanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, polyethylene glycol, and polypropylene glycol; Haloalkanes such as chloroform and carbon tetrachloride; Examples of the organic solvent include amides such as dimethylformamide, dimethylacetamide, etc. The amount of the organic solvent used is preferably adjusted so that the concentration of the reaction solution is 20 to 80% by mass.

[0047] The physical properties of the (B) component include, for example, a (meth)acrylic equivalent of 200 to 270 g / eq. By setting the content within this range, the scratch resistance of the cured product tends to be excellent. From the same point of view, the (meth)acrylic equivalent of the (B) component is preferably 210 to 250 g / eq.

[0048] Other physical properties of the component (B) include, for example, the hydroxy group concentration and the weight average molecular weight.

[0049] The hydroxyl group concentration of the (B) component is preferably 1.1 to 5 mmol / g, more preferably 3 to 5 mmol / g, and even more preferably 4 to 5 mmol / g. When the hydroxyl group concentration of the (B) component is within this range, the scratch resistance of the cured product tends to be excellent. Here, the hydroxyl group concentration is a value represented by the molar amount of hydroxyl groups contained in 1 g of the (B) component.

[0050] The weight average molecular weight of component (B) is preferably from 5,000 to 200,000, and more preferably from 20,000 to 100,000. When the weight average molecular weight of component (B) is within this range, the resin composition has an appropriate viscosity, and the cured product tends to have excellent scratch resistance.

[0051] The content of the (B) component relative to 100% by mass of the resin composition is preferably from 1 to 99% by mass, more preferably from 3 to 97% by mass, even more preferably from 5 to 95% by mass, particularly preferably from 5 to 45% by mass, and especially preferably from 5 to 40% by mass, because this increases the hardness of the cured product and also facilitates excellent scratch resistance.

[0052] The content ratio of the (A) component and the (B) component ([(A) / (B)]), in terms of the non-volatile mass, is preferably 1 / 99 to 99 / 1, more preferably 3 / 97 to 97 / 3, even more preferably 5 / 95 to 95 / 5, particularly preferably 55 / 45 to 95 / 5, and especially preferably 60 / 40 to 95 / 5, because this increases the hardness of the cured product and also facilitates excellent scratch resistance.

[0053] The resin composition of the present invention may further contain a photopolymerization initiator (C) (hereinafter referred to as component (C)).

[0054] The component (C) is classified into radical photopolymerization initiators, cationic photopolymerization initiators, anionic photopolymerization initiators, etc. These may be used alone or in combination of two or more.

[0055] Examples of the radical photopolymerization initiator include benzyl dimethyl ketals such as 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyalkylphenones such as 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)benzyl]phenyl}-2-methylpropan-1-one, and 1-hydroxycyclohexyl phenyl ketone; alkylphenone-type photopolymerization initiators such as α-aminoalkylphenones such as 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone; Acylphosphine oxide type photopolymerization initiators such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; Hydrogen abstraction type photopolymerization initiators such as phenylglyoxylic acid methyl ester; Examples of the photopolymerization initiator include oxime ester type photopolymerization initiators such as 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime)], ethanone, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime). These may be used alone or in combination of two or more.

[0056] Examples of the cationic photopolymerization initiator include a mixture of iodonium, (4-methylphenyl) [4- (2-methylpropyl) phenyl]-hexafluorophosphate (1-) and propylene carbonate, triarylsulfonium hexafluorophosphate, triarylsulfonium tetrakis- (pentafluorophenyl) borate, etc. These may be used alone or in combination of two or more.

[0057] Examples of the anionic photopolymerization initiator include cobalt amine complexes, o-nitrobenzyl alcohol carbamic acid esters, oxime esters, etc. These may be used alone or in combination of two or more.

[0058] Examples of commercially available products of the component (C) include "Omnirad 651", "Omnirad 2959", "Omnirad127", "Omnirad184", "Omnirad907", "Omnirad 369E", "Omnirad 379EG", "Omnirad TPO H", "Omnirad 819", "Omnirad MBF", "Omnicat 250", "Omnicat 270" (all manufactured by IGM Resins), "IRGACURE OXE 01", "IRGACURE 290" (all manufactured by BASF Japan Ltd.), etc. These may be used alone or in combination of two or more kinds.

[0059] Among the components (C), radical photopolymerization initiators are preferred, alkylphenone-type photopolymerization initiators are more preferred, and α-hydroxyalkylphenones are even more preferred, because the resin composition is easily cured.

[0060] The content of the component (C) relative to 100% by mass of the resin composition is preferably 10% by mass or less, and more preferably from 0.1 to 9% by mass.

[0061] The resin composition of the present invention may further contain a surfactant (D) (hereinafter referred to as component (D)).

[0062] The component (D) is classified into cationic surfactants, anionic surfactants, nonionic surfactants, reactive surfactants, etc. These may be used alone or in combination of two or more.

[0063] Examples of cationic surfactants include quaternary ammonium surfactants such as cetyltrimethylammonium chloride, alkyltrimethylammonium chloride, lauryltrimethylammonium chloride, benzalkonium chloride, stearyltrimethylammonium chloride, cetyltrimethylammonium bromide, and stearyltrimethylammonium bromide; and amidoamine surfactants such as diethylaminoethylamide stearic acid and dimethylaminopropylamide stearic acid. Examples of commercially available products include "Catiogen H" and "Catiogen L" (both manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "Cortamin 24P", "Cortamin 86P Conk", "Cortamin 60W", and "Cortamin 86W" (both manufactured by Kao Corporation). These may be used alone or in combination of two or more.

[0064] Examples of anionic surfactants include rosin acid salts such as potassium rosinate and sodium rosinate; fatty acid salts such as potassium oleate, potassium laurate, sodium laurate, sodium stearate, potassium stearate, coconut oil fatty acid triethanolamine, and triethanolamine laurate; acylated sarcosine salts such as sodium lauroyl sarcosine; alkyl sulfates such as sodium lauryl sulfate, ammonium lauryl sulfate, and triethanolamine lauryl sulfate; alkyl ether sulfates such as polyoxyethylene alkyl ether sulfate; amide sulfates such as sodium polyoxyethylene coconut oil fatty acid monoethanolamide sulfate; alkyl aryl sulfonates such as triethanolamine dodecylbenzenesulfonate; sulfosuccinic acid esters such as dioctyl sulfosuccinate, polyoxyethylene lauryl disodium sulfosuccinate, and lauryl disodium sulfosuccinate; alkyl phosphate esters such as lauryl phosphate; and alkyl ether phosphate esters such as polyoxyethylene lauryl ether phosphate and polyoxyethylene oleyl ether phosphate. These may be used alone or in combination of two or more.

[0065] Examples of nonionic surfactants include ethers such as polyoxyethylene alkyl ethers and polyoxyethylene polyoxypropylene alkyl ethers, esters such as polyethylene glycol alkyl esters and sorbitan fatty acid esters, ether esters such as polyoxyethylene sorbitan aliphatic esters, amino ethers such as polyoxyethylene alkyl amines, alkanol amides such as aliphatic monoethanolamides and aliphatic diethanolamides, etc. These may be used alone or in combination of two or more.

[0066] Examples of the reactive surfactant include those described in JP-A-2003-293288. In addition, examples of commercially available products include "Latemul S-180A", "Latemul PD-104", "Latemul PD-105", "Latemul PD-420", and "Latemul PD-430" (all manufactured by Kao Corporation), "Eleminol JS-2" (all manufactured by Sanyo Chemical Industries, Ltd.), "Aqualon KH-10", "Aqualon BC-20", "Aqualon RN-20", "Aqualon RN-30", and "Aqualon RN-50" (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), "ADEKA REASOAP SE-10N" and "ADEKA REASOAP SR-10N" (all manufactured by ADEKA Corporation), trade names "Antox MS-60" and "Aminoion RE-1000L" (all manufactured by Nippon Nyukazai Co., Ltd.), "Surfmer FP-120" (all manufactured by Toho Chemical Industry Co., Ltd.), and "BYK-UV-3500" (all manufactured by BYK-Chemie Japan). These may be used alone or in combination of two or more.

[0067] The content of the component (D) relative to 100% by mass of the resin composition is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0068] The resin composition of the present invention may further contain a solvent and additives other than those mentioned above.

[0069] Examples of the solvent include water such as ultrapure water, pure water, ion-exchanged water, industrial water, tap water, etc.; the above-mentioned organic solvents, etc. These may be used alone or in combination of two or more kinds.

[0070] Examples of additives include resins such as acrylic resins, epoxy resins, and urethane resins; ultraviolet absorbers, antioxidants, silicones, siloxanes, silanes, antistatic agents, antifogging agents, rheology control agents, fillers, release agents, flame retardants, viscosity regulators, plasticizers, antibacterial agents, antifungal agents, defoamers, colorants, stabilizers, pigments, surface conditioners, catalysts, and photosensitizers. These may be used alone or in combination of two or more.

[0071] The resin composition of the present invention can be obtained by mixing the components (A) and (B), and optionally the components (C) and (D), a solvent, and additives at room temperature. When mixing, the mixture may be heated or cooled as appropriate.

[0072] The resin composition of the present invention can be used as a resin composition for hard coating or a resin composition for release coating.

[0073] The hard coat resin composition and release coating resin composition of the present invention are used when applying to a substrate described later, and are cured by a curing method described later to form a cured film (cured film).

[0074] When the resin composition of the present invention is used as a resin composition for hard coat, examples of applicable applications include the main bodies and remote controls of home appliances such as refrigerators, televisions, and air conditioners; housings and displays of information terminals such as mobile phones, smartphones, tablets, and personal computers; and plastic molded products such as automobile parts and automobile interior materials.

[0075] When the resin composition of the present invention is used in a release coating composition, examples of the use include the production of protective films for the adhesive surfaces of adhesive tapes, pressure-sensitive adhesive tapes, double-sided tapes, pressure-sensitive adhesive labels, stickers, etc.; the adhesive surfaces of separators, etc.; resin molded products, synthetic leather, decorative panels, carbon fiber prepregs, electric and electronic parts, etc. Here, electrical and electronic components refer to components that make up products that have electronic circuits, such as personal computers, mobile phones, liquid crystal displays, refrigerators, and automobiles.

[0076] The resin composition of the present invention can also be used in other applications in which it can exert a desired effect.

[0077] The present invention also relates to a cured product of the resin composition.

[0078] The cured product of the present invention can be obtained by applying the resin composition to a substrate described below and curing the composition.

[0079] Examples of the substrate include: Metals such as gold, silver, copper, tin, nickel, aluminum, titanium, molybdenum, zinc, cobalt, nickel, chromium iron-nickel-cobalt alloy, tungsten, copper-tungsten, Invar, Galvalume steel sheet (registered trademark), ZAM steel sheet, etc.; Olefins such as polyethylene, polypropylene, and norbornene; Polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); acrylics such as polymethyl methacrylate (PMMA); Vinyls such as polyvinyl chloride, polyvinylidene chloride, and polyvinyl alcohol; Polystyrenes include polystyrene (PS), styrene-acrylonitrile (AS), and styrene-butadiene-acrylonitrile (ABS); Examples of the material include polycarbonate, polyamide (nylon), polyether ether ketone (PEEK), polyimide, epoxy resin, melamine resin, triacetyl cellulose, etc. These may be used alone or in combination of two or more.

[0080] The substrate may be subjected to surface treatment such as corona discharge, metal deposition, plating, etc.; rust prevention treatment such as mirror finishing; or chemical conversion treatment. Examples of surface treatment include treatment with a plating solution containing Ni, Zn, Sn, etc.; treatment with zirconium phosphate; chromate treatment with chromate phosphate or chromate chromate, etc. In addition, other layers such as an easy-adhesion layer, an anchor layer, etc. may be provided between the cured product of the resin composition formed on one or both sides of the substrate.

[0081] The thickness of the substrate is preferably 1 to 2,000 μm.

[0082] Examples of the coating method include a bar coater, a Mayer bar, an air knife, gravure, reverse gravure, offset printing, flexographic printing, screen printing, flow coating, etc. The coating amount is 1 to 1,000 g / m2 in terms of the thickness of the cured product after curing. 2 is preferred.

[0083] The curing method may be activation energy rays, heat, or the like.

[0084] The curing method using active energy rays may be, for example, a method using a light source (wavelength range: 150 to 450 nm) such as a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a xenon lamp, a chemical lamp, an electrodeless discharge lamp, or an LED, with an intensity of 10 to 10,000 mJ / cm. 2 and the like. Before irradiation with active energy rays, the coating may be dried by heating as necessary. Furthermore, after irradiation with active energy rays, the coating may be completely cured by heating as necessary. Examples of heat sources include a circulating air dryer and a heating furnace. Drying conditions by heating are usually at a temperature of 60 to 150°C for 1 second to 30 minutes, and preferably at a temperature of 70 to 130°C for 5 seconds to 10 minutes. Furthermore, curing conditions by heating are usually at a temperature of 150 to 250°C for 1 second to 30 minutes, and preferably at a temperature of 170 to 220°C for 30 seconds to 20 minutes.

[0085] The thickness of the cured product after curing is preferably 0.01 to 100 μm.

[0086] The laminate of the present invention includes a substrate and the cured product. The substrate, coating method, curing method, etc. may be the same as those described above.

[0087] The laminate of the present invention may be subjected to a curing treatment as required. The conditions for the curing treatment include temperature, The curing temperature is 20 to 50° C. and the curing time is 1 to 24 hours. The curing treatment tends to further improve the solvent resistance of the cured product.

[0088] <Manufacturing method for recycled materials> Since the cured product of the present invention has excellent solubility in an alkaline solution, when the cured product forms a laminate (substrate-cured product-other layer) with a substrate or other layer, the cured product can be dissolved by contacting the cured product with an alkaline solution, and the substrate can be recycled. Examples of methods for using the recycled substrate include a method of using the substrate as it is again, a method of subjecting the substrate to chemical or physical treatment, and a method of manufacturing and using the substrate again.

[0089] Examples of a method for recycling a substrate from the laminate of the present invention (a method for producing a recycled substrate) include: (1) a step of contacting the laminate with an alkaline solution to remove the cured material; (2) separating the substrate; (3) Reproducing the raw material of the substrate from the separated substrate; (4) producing a substrate from a substrate raw material; The recycled substrate refers to a substrate from which the cured material has been removed by dissolving it in an alkaline solution from the laminate. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following description, parts and % are based on mass.

[0091] The weight average molecular weight (Mw) of the (meth)acrylic copolymer was measured by gel permeation chromatography (GPC) under the following conditions. (GPC measurement conditions) Model: Device name - HLC-8220 (Tosoh Corporation) Column: Product name: TSKgel SuperHM-L (Tosoh Corporation) x 3 Developing solvent: Tetrahydrofuran

[0092] Synthesis Example 1 A reactor equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen inlet tube was charged with 32.6 parts of glycidyl methacrylate (hereinafter also referred to as GMA), 48.6 parts of butyl acetate, and 1.5 parts of azobisisobutyronitrile (hereinafter also referred to as AIBN), and then heated to about 100°C under a nitrogen flow and kept at that temperature for 10 hours. The mixture was cooled to 60°C, and 16.6 parts of acrylic acid, 0.5 parts of methoquinone, and 0.1 parts of triphenylphosphine were added, and the mixture was heated to 110°C under air bubbling and reacted for 9 hours to obtain a (meth)acrylic copolymer (B-1) with a non-volatile content of 50%. The obtained (B-1) component had a hydroxy group concentration of 3.8 mmol / g, a (meth)acrylic equivalent of 214 g / eq, and a weight average molecular weight of 30,000.

[0093] Comparative synthesis example 1 In a reaction apparatus similar to that of Synthesis Example 1, 32.6 parts of GMA, 32.6 parts of methyl methacrylate (trade name: "Methyl Methacrylate", manufactured by Kuraray Co., Ltd.), 97.2 parts of butyl acetate, and 3.0 parts of AIBN were charged, and the mixture was heated to about 100°C under a nitrogen stream and kept at that temperature for 10 hours. The mixture was cooled to 60°C, and 16.6 parts of acrylic acid, 1.0 parts of methoquinone, and 0.2 parts of triphenylphosphine were added, and the mixture was heated to 110°C under air bubbling and reacted for 9 hours to obtain a (meth)acrylic copolymer solution (E-1) with a non-volatile content of 50%. The obtained (E-1) component had a hydroxyl group concentration of 5.1 mmol / g, an acrylic equivalent of 290 g / eq, and a weight average molecular weight of 30,000.

[0094] Example 1 95.0 parts of glycerin di / triacrylate (trade name: "Aronix M-920", manufactured by Toagosei Co., Ltd., viscosity: 40 mPa s, hydroxyl value: 240 mgKOH / g), 5.0 parts of the component (B-1) obtained in Synthesis Example 1, and 5.0 parts of 1-hydroxycyclohexyl phenyl ketone (trade name: "Omnirad 184", manufactured by IGM Resins) as a photopolymerization initiator were blended, diluted with methyl ethyl ketone to a nonvolatile concentration of 30%, and mixed uniformly to obtain a resin composition (1).

[0095] Examples 2 to 8, Comparative Examples 1 to 11 The same procedure as in Example 1 was carried out except that the compositions were changed as shown in Table 1 below, to obtain resin compositions (2) to (8) and (1') to (11'), respectively.

[0096] <Preparation of Laminate> Each resin composition was applied to a polyethylene terephthalate film (thickness: 100 μm) using a bar coater, dried at 80 °C for 1 minute, and then exposed to light from a high-pressure mercury lamp (output: 120 W / cm) at an irradiation distance of 15 cm, a belt speed of 7 m / min, and an accumulated light intensity of 300 mJ / cm. 2 The resulting mixture was cured under the above conditions to prepare laminates.

[0097] (Scratch resistance) Each laminate was set in a commercially available measuring device (product name "Flat Abrasion Tester", manufactured by Daiei Scientific Instruments Co., Ltd.), and the surface of each cured product was scratched 10 times back and forth with a load of 100 g using steel wool (number "#0000", grade "extra fine", manufactured by Nippon Steel Wool Co., Ltd.) The scratch resistance of the laminate was evaluated based on the number of scratches made, according to the following criteria. AAA: No scratches at all AA: 1 or more scratches, less than 5 scratches A: 5 or more scratches, less than 10 scratches B: 10 or more scratches

[0098] (removability) After each laminate was allowed to stand under conditions A and B, the removability of the cured product was evaluated according to the following evaluation criteria. Condition A: 2N sodium hydroxide solution, left at 50℃ for 30 minutes Condition B: 0.5N sodium hydroxide solution, left at 50℃ for 30 minutes ◯: The hardened material was completely removed. ×: The cured product was not removed.

[0099] [Table 1]

[0100] The terms in Table 1 refer to the following components. Glycerin di / triacrylate - Product name: "Aronix M-920", manufactured by Toagosei Co., Ltd., Viscosity: 40 mPa·s, Hydroxyl value: 240 mgKOH / g Glycerin triacrylate - Product name: "Aronix M-930", manufactured by Toagosei Co., Ltd., Viscosity: 30 mPa·s, Hydroxyl value: 30 mgKOH / g Carboxylic acid-containing pentaerythritol acrylate - Product name: "Aronix M520", manufactured by Toagosei Co., Ltd. Sorbitol 6EO acrylate - Product name: "Aronix M926", manufactured by Toagosei Co., Ltd. Pentaerythritol tri / tetraacrylate - Product name: "Aronix M305", manufactured by Toagosei Co., Ltd. Ethoxylated glycerin triacrylate - Product name: "A-GLY-9E", manufactured by Shin-Nakamura Chemical Co., Ltd. Bisphenol A EO modified diacrylate - Product name: "Mirmaer M240", manufactured by MIWON Omnirad184-1-Hydroxycyclohexyl phenyl ketone, trade name: "Omnirad184", manufactured by IGM Resins BYK-UV-3500 - Silicone-based surface conditioner, product name: "BYK-UV-3500", manufactured by BYK

Claims

1. A (meth)acrylate (A) containing a poly(meth)acrylate (a1) having no carboxyl group and a hydroxy group and having a weight average molecular weight of 170 or more and 250 or less; and The resin composition comprises a (meth)acrylic copolymer (B) having a (meth)acrylic equivalent of 200 to 270 g / eq, the (meth)acrylic copolymer (B) being a reaction product of a polymer (b1) that is a polymerization component containing an unsaturated monomer having an epoxy group and an α,β-unsaturated carboxylic acid (b2).

2. 2. The resin composition according to claim 1, wherein a content ratio of the component (A) to the component (B) [component (A) / component (B)] is 5 / 95 to 95 / 5 in terms of non-volatile mass.

3. A resin composition for hard coat comprising the resin composition according to claim 1 or 2.

4. A release coating composition comprising the resin composition according to claim 1 or 2.

5. A cured product of the resin composition according to claim 1 or 2.

6. A laminate comprising a substrate and the cured product according to claim 5 .

7. A method for producing a recycled substrate, comprising the step of removing the cured product according to claim 5 by contacting the laminate according to claim 6 with an alkaline solution.

Citation Information

Patent Citations

  • Recycling system and method for regenerating plastic laminates into recycled materials, and method for separating and recovering laminates

    JP2022068217A

  • Polymer Recycling

    JP2022544275A